Les racines et tubercules en Haiti - Tremblay, A.; Pierre-jean, L. (International Center for Tropical Agriculture, 1986)
The existing data on production and consumption of sweet potato, cassava, yam, potato, taro, and arum crops are presented to provide basic elements with which the problems of these crops in Haiti can be analyzed. Ecosystems in which they are grown, farm characteristics, required labor, cropping systems, and production costs, vol., and constraints are indicated. The processing and marketing of the products, the domestic demand for fresh and processed products, and their constraints are also discussed. It should be noted that these crops are consumed only locally. Government policies are analyzed and the institutions, personnel, training, and budget involved in research are described. Finally, some recommendations on an approach toward research are made. (CIAT)